ANALISIS BAURAN PEMASARAN DALAM PERANANNYA MEMOTIVASI CALON MAHASISWA Studi Kasus Pemasaran di UNISMA - Ridwan Lutfiadi; Nana Danapriatna; U. Maman Rubaman; Rony Setiawan (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2005)
To reach for the amount of adequate students to a lecturing process, UNISMA conduct assumed marketing strategy isn't it can improve the amount of new students. UNISMA conduct marketing mix (product, price, location, and promotion) in strategy marketing of him, but student respon to conducted by strategy and which factor is which most dominant in marketing not yet been mapped Target of this research is to know student segment, perception of student, and most dominant fator in conducted by marketing mix strategy. Result of research indicate that student of UNISMA most coming from circles of midle segment, marketing mix UNISMA was responded either by student, and from fourth of marketing mix, only price factor and most dominant product which motivate student candidate enter UNISMA.